The C4 region as a target for HIV entry inhibitors – NMR mapping of the interacting segments of T20 and gp120. (22nd October 2015) - Moseri, Adi; Biron, Zohar; Arshava, Boris; Scherf, Tali; Naider, Fred; Anglister, Jacob
Abstract : The peptide T20, which corresponds to a sequence in the C‐terminal segment of the HIV‐1 transmembrane glycoprotein gp41, is a strong entry inhibitor of HIV‐1. It has been assumed that T20 inhibits HIV‐1 infection by binding to the trimer formed by the N‐terminal helical region (HR1) of gp41, preventing the formation of a six helix bundle by the N‐ and C‐terminal helical regions of gp41. In addition to binding to gp41, T20 was found to bind to gp120 of X4 viruses and this binding was suggested to be responsible for an alternative mechanism of HIV‐1 inhibition by this peptide. In the present study, T20 also was found to bind R5 gp120. Using NMR spectroscopy, the segments of T20 that interact with both gp120 and a gp120/CD4M33 complex were mapped. A peptide corresponding to the fourth constant region of gp120, sC4, was found to partially recapitulate gp120 binding to T20 and the segment of this peptide interacting with T20 was mapped. The present study concludes that an amphiphilic helix on the T20 C‐terminus binds through mostly hydrophobic interactions to a nonpolar gp120 surface formed primarily by the C4 region. The ten‐ to thousand‐fold difference between the EC50 of T20 against viral fusion and the affinity of T20 to gp120 implies that binding to gp120 is not a major factor in T20 inhibition of HIV‐1 fusion. Nevertheless, this hydrophobic gp120 surface could be a target for anti‐HIV therapeutics. Abstract : Enfuvirtide (T20) is a peptide of the HIV‐1 transmembrane glycoprotein gp41 that inhibits HIV‐1 entry by interfering with the formation of the six‐helix bundle by gp41. In addition, T20 was shown to bind gp120 of X4 viruses. Anglister and colleagues now report that T20 also binds to the gp120 protein of R5 viruses that cause the majority of HIV‐1 infections. This binding was mapped to specific residues in T20 and the C4 region of gp120 using solution NMR techniques. The identified gp120 binding surface could be a target for anti‐HIV therapeutics. This article is accompanied by a podcast, listen now . Orlisten in iTunes .